Malaysian university students’ attitudes towards six varieties of accented speech in English - Thamer Ahmed, Zainab; Abdullah, Ain Nadzimah; Chan, Swee Heng (Australian International Academic Centre, 2014)
Previous language attitude studies indicated that in many countries all over the world, English language learners perceived native accents either American or British, more positively than the non-native accents such as the Japanese, Korean, and Austrian accents. However, in Malaysia it is still unclear which accent Malaysian learners of English tend to perceive more positively (Pillai 2009). The verbal-guise technique and accent recognition item were adopted as indirect and direct instruments in gathering data to obtain data to clarify the inquiry. The sample includes 120 Malaysian university students and they were immersed in several speech accent situations to elicit feedback on their perceptions. Essentially two research questions are addressed: 1) What are Malaysian university students’ attitudes toward native and non-native English accents? 2) How familiar are students with accents? The results indicated that the students had a bias towards in-group accent, meaning that they evaluated non-native lecturers’ accents more positively. These results supported the ‘social identity theory’ consistent with many previous language attitude studies of this nature. The Malaysian students were seen to be able to distinguish between native and non-native accents although there was much confusion between British and American accents.